2023
DOI: 10.1002/cam4.6344
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum uric acid and prostate cancer mortality in androgen deprivation therapy: A population‐based cohort study

Abstract: ObjectiveThis population‐based study examined the association between baseline uric acid (UA) and prostate cancer (PCa)‐related mortality amongst PCa patients receiving androgen deprivation therapy (ADT).MethodsAdults with PCa who received ADT in Hong Kong between December 1999 and March 2021 were identified. Patients with missing baseline UA were excluded. Patients were followed up until September 2021. The outcome was PCa‐related mortality.ResultsAltogether, 4126 patients (median follow‐up 3.1[interquartile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Similar studies have shown that uric acid plays dual roles; for example, moderate elevations in SUA at low concentrations can improve diabetic complications and can lead to the aggravation of diabetes. The SUA level has a “J” shaped relationship with the risk of death associated with prostate cancer with the risk of death decreasing and then increasing as SUA levels rise. High levels of SUA are protective against neurological disorders, such as Parkinson’s disease, whereas low levels are harmful. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar studies have shown that uric acid plays dual roles; for example, moderate elevations in SUA at low concentrations can improve diabetic complications and can lead to the aggravation of diabetes. The SUA level has a “J” shaped relationship with the risk of death associated with prostate cancer with the risk of death decreasing and then increasing as SUA levels rise. High levels of SUA are protective against neurological disorders, such as Parkinson’s disease, whereas low levels are harmful. …”
Section: Discussionmentioning
confidence: 99%
“…High uric acid levels can cause inflammation and oxidative stress, promote the death of pancreatic β-cells, and induce diabetes in male mice . However, an appropriate increase in uric acid at low concentrations may improve short-term functional outcomes of ischemic stroke in patients with type 2 diabetes and reduce the risk of death associated with prostate cancer . Moreover, at physiological concentrations, uric acid acts as an antioxidant, scavenging oxygen radicals and exerting a protective effect on most organs, , except the nervous system .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The long‐term effects of ADT on insulin sensitivity need further investigation. Other metabolic risk factors include raised uric acid levels [ 34 ]. Finally, in a subgroup analysis of patients with prostate cancer receiving ADT who also had diabetes, visit‐to‐visit variability in HbA1c was a significant prognostic marker [ 35 ], and metformin use was protective against adverse cardiovascular outcomes and mortality [ 36 , 37 ].…”
Section: Androgen Deprivation Therapy‐related Cardiovascular Toxicitymentioning
confidence: 99%